Farmer response to rationed and uncertain irrigation supplies - Perry, C.J.; Narayanamurthy, S.G. (International Water Management Institute, 1998)
Explores the theoretical and actual responses of farmers faced with irrigation supplies that are limited in relation to available land and labor resources, and where the actual schedule and available volume for delivery are uncertain.